1986
DOI: 10.1038/bjc.1986.274
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cytotoxicity of vindesine and cis-platinum for human lung tumours by the use of verapamil in vitro

Abstract: The use of verapamil, a calcium channel antagonist, to circumvent established resistance in human cancer cell lines has been reported for lung (Fetherston et al., 1985) and ovary (Rogan et al., 1984) using adriamycin and the vinca alkaloids. We were interested in its potential use for the enhancement of cytotoxicity of vindesine and cisplatinum in non-small cell cancer of lung (NSCCL). An earlier study (Simmonds et al., 1986) using primary patient material in clonogenic assay has confirmed the overall poor cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Similarly the combined use of verapamil and cisplatin in neuroblastoma transplanted to BLAB/c athymic mice leads to a more marked decrease in tum'our growth than cisplatin alone (Ikeda et al 1987). One study using human tumour cells has confirmed the results in experimental animals, as verapamil was observed to enhance cisplatin cytotoxicity in 50% of tumour samples from previously untreated patients with non-small cell lung carcinoma (Simmonds et a/. 1986).…”
Section: Interaction With Cisplatin and Melphalanmentioning
confidence: 93%
“…Similarly the combined use of verapamil and cisplatin in neuroblastoma transplanted to BLAB/c athymic mice leads to a more marked decrease in tum'our growth than cisplatin alone (Ikeda et al 1987). One study using human tumour cells has confirmed the results in experimental animals, as verapamil was observed to enhance cisplatin cytotoxicity in 50% of tumour samples from previously untreated patients with non-small cell lung carcinoma (Simmonds et a/. 1986).…”
Section: Interaction With Cisplatin and Melphalanmentioning
confidence: 93%
“…In the context of enhancement of drug sensitivity this concentration of verapamil is at the lower end of the dose-response curve, but some studies (Yalowich & Ross, 1984;Slater et al, 1986;Supino et al, 1986) do indicate that verapamil may enhance sensitivity to adriamycin and VP16 at concentrations of 1-2pM in vitro. These concentrations of verapamil in vitro have also been reported to enhance tumour cell sensitivity to vinca alkaloids (Tsuruo et al, 1981;Tsuruo et al, 1983a;Simmonds et al, 1986) and daunorubicin (a structural analogue of adriamycin; Slater et al, 1982). In vivo, using animal ascites tumour models, verapamil has been reported to enhance sensitivity to VP16 (Slater et al, 1986), daunorubicin (Slater et al, 1982) and vincristine (Tsuruo et al, 1981).…”
mentioning
confidence: 99%
“…29], vinca alkaloids [2], etoposide [25. 26] melphalan [21] and cis-platinum [12,27], These studies were per formed in drug-responsive and nonresponsive tumors of both murine and human origin [9,10,31].…”
Section: Introductionmentioning
confidence: 99%